Pride in ethnic language and numerical dominance: A case study of the Iban in Sarawak, Malaysia - Lilly, Metom; Ting, Su Hie (2022)
Indigenous speech communities usually experience language shift because of their smaller population in relation to other ethnic groups, who may hold more political power and whose languages may have official language status. Past research has indicated that smaller groups tend to experience hastened shift away from their ethnic languages compared to bigger groups. If the indigenous group is living in an area where they are the dominant group such as the Iban in Song, a rural town in Sarawak, Malaysia, then their language is still somewhat a lingua franca. Ting, Tinggang, and Metom (2021) found that Iban is still widely used in these six domains: family, friendship, transactions, religious, employment, and education (when it involves informal interactions). The Iban people have positive attitudes but are speaking more Malay than the older generation. The question is whether the Iban people living among other ethnic groups outside of their home-ground have strong positive attitudes that can motivate them to extensively speak their language. The study investigated how pride in the Iban language is influenced by the numerical dominance of the Iban community in in Sarawak, Malaysia.